Theoretical study of the α+d→6Li+γ astrophysical capture process in a three-body model. II. Reaction rates and primordial abundance - Tursunov, E.; Turakulov, S.; Kadyrov, Alisher; Bray, Igor (The American Physical Society, 2018)
The astrophysical S factor and reaction rate of the direct capture process a+d?Li6+?, as well as the abundance of the Li6 element, are estimated in a three-body model. The initial state is factorized into the deuteron bound state and the a+d scattering state. The final nucleus Li6(1+) is described as a three-body bound state a+n+p in the hyperspherical Lagrange-mesh method. Corrections to the asymptotics of the overlap integral in the S and D waves have been done for the E2 S factor. The isospin forbidden E1 S factor is calculated from the initial isosinglet states to the small isotriplet components of the final Li6(1+) bound state. It is shown that the three-body model is able to reproduce the newest experimental data of the LUNA Collaboration for the astrophysical S factor and the reaction rates within the experimental error bars. The estimated Li6/H abundance ratio of (0.67±0.01)×10-14 is in a very good agreement with the recent measurement (0.80±0.18)×10-14 of the LUNA Collaboration.